Incident reports involving hospital administrative staff: analysis of data from the Japan Council for Quality Health care nationwide database - Naomi Akiyama; Tomoya Akiyama; Kenshi Hayashida; Takeru Shiroiwa; Keisuke Koeda (BMC, 2020)
Abstract Background Task shifting and task sharing in health care are rapidly becoming more common as the shortage of physicians increases. However, research has not yet examined the changing roles of hospital administrative staff. This study clarified: (1) the adverse incidents caused by hospital administrative staff, and the direct and indirect impact of these incidents on patient care; and (2) the incidents that directly involved hospital administrative staff. Methods This study used case report data from the Japan Council for Quality Health care collected from April 1, 2010 to March 31, 2019, including a total of 30,823 reports. In April 2020, only the 88 self-reported incidents by hospital administrative staff were downloaded, excluding incidents reported by those in medical and co-medical occupations. Data from three reports implicating pharmacists were rejected and the quantitative and textual data from the remaining 85 case reports were analyzed in terms of whether they impacted patient care directly or indirectly. Results Thirty-nine reports (45.9%) involved direct impact on patient care, while 46 (54.1%) involved indirect impact on patient care. Most incidents that directly impacted patient care involved administrative staff writing prescriptions on behalf of a doctor (n = 24, 61.5%); followed by errors related to system administration, information, and documentation (n = 7, 17.9%). Most reported errors that indirectly affected patient care were related to system administration, information, and documentation used by administrative staff (n = 22, 47.8%), or to reception (n = 9, 19.6%). Almost all errors occurred during weekdays. Most frequent incidents involved outpatients (n = 23, 27.1%), or occurred next to examination/operation rooms (n = 12, 14.1%). Further, a total of 14 cases (16.5%) involved patient misidentification. Conclusions Incidents involving hospital administrative staff, the most common of which are medication errors from incorrect prescriptions, can lead to severe consequences for patients. Given that administrative staff now form a part of medical treatment teams, improvements in patient care may require further submission and review of incident reports involving administrative staff.